2016
DOI: 10.1161/atvbaha.116.307985
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Cocaine Use, and Hepatitis C Virus

Abstract: Objective We assessed cross-sectional and longitudinal associations of 3 non-traditional cardiovascular disease (CVD) risk factors - human immunodeficiency virus (HIV), cocaine use, and chronic hepatitis C virus (HCV) infection - with 3 validated markers of subclinical CVD: carotid artery plaque, albuminuria, and aortic pulse wave velocity (PWV) in a well-characterized cohort. Approach and Results We measured carotid plaque at baseline and after 24 months, urine albumin-creatinine ratio (ACR) every 6 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Lai et al [95,96,97] also showed this association in their earlier studies. Similarly, Lucas et al [92] found greater carotid plaque formation at baseline among cocaine users compared with cocaine nonusers. This variability in findings across studies regarding association between cocaine use and subclinical CAD might be explained by different CAD risk factor profiles of the study populations.…”
Section: Cocaine Cardiotoxicity In Human Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Lai et al [95,96,97] also showed this association in their earlier studies. Similarly, Lucas et al [92] found greater carotid plaque formation at baseline among cocaine users compared with cocaine nonusers. This variability in findings across studies regarding association between cocaine use and subclinical CAD might be explained by different CAD risk factor profiles of the study populations.…”
Section: Cocaine Cardiotoxicity In Human Studiesmentioning
confidence: 94%
“…Chronic cocaine users were at significantly higher risk for the presence of CAC (propensity score-adjusted PR = 1.26, 95% CI: 1.05–1.52), any coronary stenosis (propensity score-adjusted PR = 1.30, 95% CI: 1.08–1.57), and calcified plaques (propensity score-adjusted PR = 1.37, 95% CI: 1.10–1.71), in addition to subclinical CAD. Another study conducted by Lucas et al [92] showed a significant association between cocaine use and carotid plaque formation. More than 90% of subjects in this study were African Americans.…”
Section: Cocaine Cardiotoxicity In Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Illicit drug use is associated with a myriad of health conditions, including human immunodeficiency virus (HIV), hepatitis C virus (HCV), hepatitis B virus (HBV), heart disease, liver disease, soft tissue infections, hypertension, and depression(Centers for Disease Control and Prevention (CDC), 2001; Chen, Huang, Yeh, & Chien, 2015; Coughlin & Shang, 2011; D C Des Jarlais et al, 2007; Doherty et al, 1996; Kessler et al, 1996; Lucas et al, 2016; Stein, 1999; Walker, Pratt, Schoenborn, & Druss, 2016)). Despite being at increased risk for several co-morbidities, people who use drugs (PWUDs), compared with the general population, are more likely to delay seeking medical care when necessary, are less likely to utilize primary medical care and are more likely to utilize emergency rooms as their primary source of care (Chen et al, 2015; Chitwood, McBride, French, & Comerford, 1999; French, McGeary, Chitwood, & McCoy, 2000; McGeary & French, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 25% of the HIV subjects had a history of cocaine exposure compared to only 4% of controls, and hepatitis C infection was present in 18% of the HIV subjects. Non-traditional risk factors for atherosclerotic disease such as cocaine and chronic hepatitis C infection are associated with carotid plaque in HIV 8 . Further, chronic cocaine use was associated with a 2-fold increased risk of coronary artery plaque in HIV, independent of traditional risk factors and ART exposure 9 .…”
mentioning
confidence: 99%